The influence of lower-limb prostheses technology on Paracanoeing time-trial performance. (18th August 2018) - Ellis, Shelley; Callaway, Andrew; Dyer, Bryce
Abstract: Within the Paracanoeing discipline, it is important to ensure that appropriate control is achieved by a paddler with a disability. However, this Paralympic Games discipline has seen very little attention to date. The aims of this study were to understand the kinematic impact to a paracanoeist when not utilizing the use of a prosthetic lower-limb. A kayaker with a uni-lateral transfemoral amputation completed several 200 m maximal efforts both with and without their prosthesis. When the prosthetic limb was removed, there were significant differences found in stroke rate, stroke speed, stroke length and overall power output. Sagittal and frontal video analysis demonstrated the residual limb movements when paddling and indicated where support would be required to improve the kayak's control. It is recommended that those with lower-limb absence wishing to paddle a kayak competitively utilize the use of a prostheses designed for the kayaking environment that supports the residual limb at both the upper and inner thigh and the distal end. Implications for rehabilitation: This paper is the first study to investigate both biomechanical and assistive technology-related issues in the new Paralympic Games sport of Paracanoeing. For participants possessing lower-limb absence, a prosthetic limb that is designed specifically for the kayaking environment is recommended when Paracanoeing to maximize efficient propulsion. Use of an ergometer and multiple 2D cameras provides practitioners the ability to optimize both the comfort and fit of a prosthetic limb. Use of an ergometer and multiple 2D cameras provides both athletes and practitioners the ability to optimize the points of human contact within a kayak to ensure comfort and control.